Bi4O5I2 / Fe3O4 composite magnetic nano photocatalyst and preparation method thereof

By preparing Bi4O5I2/Fe3O4 composite magnetic nanophotocatalysts, the external magnetic field is used to achieve rapid material recovery, solving the problem of difficult recovery of powdered photocatalysts, and achieving efficient environmental protection and catalytic degradation effects.

CN119425743APending Publication Date: 2025-02-14襄阳职业技术学院
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411540028.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing powdered photocatalysts are difficult to recover after use, resulting in secondary pollution to the water environment and difficult material recycling.

Method used

Bi4O5I2/Fe3O4 composite magnetic nanophotocatalyst is used to prepare the combination of Fe3O4 nanoparticles with porous structures and BiOI solution to form a composite material with magnetic properties, and the external magnetic field is used to achieve rapid material recovery.

Benefits of technology

It realizes efficient recycling and utilization of powdered photocatalysts, avoids secondary pollution in the environment, and improves the catalytic degradation efficiency of antibiotic organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425743A_ABST
    Figure CN119425743A_ABST
Patent Text Reader

Abstract

The invention discloses a Bi4O5I2 / Fe3O4 composite magnetic nano photocatalyst and a preparation method thereof, and belongs to the technical field of photocatalysts.The preparation method comprises the steps that firstly, ferric chloride hexahydrate (FeCl3. 6H2O), sodium acetate, ethylene glycol and ethidene diamine are subjected to ultrasonic dispersion for 30 min, and then magnetic stirring is conducted for 1 h till complete dissolution is achieved; the dissolved solution is put into a stainless steel reaction kettle with polytetrafluoroethylene as an inner tank, the stainless steel reaction kettle is put into a drying oven for a reaction, after a product is obtained, the product is separated, washed and dried, and Fe3O4 magnetic nanoparticles of a porous structure are obtained; secondly, the Bi4O5I2 / Fe3O4 composite magnetic nano photocatalyst is prepared through a water dissolving method, the photocatalytic material obtained through the method has a porous magnetic nano structure and can degrade antibiotic organic pollutants (such as tetracycline hydrochloride and TCH) in water under visible light, and due to the fact that the material has the magnetic structure, the catalyst is easy to recycle after photocatalytic degradation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a Bi 4 O 5 I 2 / Fe 3 O 4 The invention relates to a composite magnetic nanometer photocatalyst and a preparation method thereof, belonging to the technical field of photocatalysts. Background Art

[0002] In recent decades, with the continuous development of animal husbandry and pharmaceutical industries, more and more antibiotics are discharged into the water in different forms, forming organic wastewater containing antibiotics. Antibiotics are difficult to be degraded by microorganisms and may even cause microorganisms to develop drug resistance. Moreover, drug-resistant genes can expand and evolve in the environment, posing a potential threat to the ecological environment and human health.

[0003] Therefore, photocatalytic technology based on semiconductor materials has attracted more and more attention due to its high efficiency and no secondary pollution. So far, a large number of photocatalytic materials have been applied in the fields of solar energy conversion and organic pollutant treatment. 4 O 5 I 2 It is a new type of high-efficiency photocatalyst that can be widely used in environmental governance because it has a narrow bandgap, good visible light response, good electrical conductivity and effective oxygen ion conductivity, and is non-toxic and easy to prepare.

[0004] For example, in the Chinese invention patent document, a CdS nanorod@few-layer ReS2 nanosheet composite photocatalyst, with the announcement number CN109954504B, mainly includes the following steps: Step 1) Prepare ReS2 by ball milling; Step 2) Disperse ReS2 powder in a solvent such as ethanol and ultrasonically exfoliate; Step 3) Centrifuge the ultrasonic dispersion, finally collect and wash the product, and freeze-dry to obtain a few-layer ReS2 nanosheet product. Step 4) Cadmium acetate dihydrate and dibenzyl disulfide are ultrasonically dispersed in deionized water and ethanol, respectively.

[0005] However, from the perspective of practical application and business, since the material is in powder form, it is difficult to recycle. After use, the material is prone to secondary pollution to the water environment. Therefore, the invention is to prepare Bi that is easy to recycle and reuse. 4 O 5 I 2 Photocatalytic materials are imminent. Summary of the invention

[0006] The purpose of the present invention is to provide a Bi 4 O 5 I 2 / Fe 3 O4 A composite magnetic nanometer photocatalyst and a preparation method thereof are provided to achieve the purpose of making it easier to recycle the powdered photocatalyst.

[0007] A kind of Bi 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nanophotocatalysts, including porous Fe 3 O 4 Nanoparticles, sodium dodecylbenzene sulfonate and BiOI solution, add alkali solution to the BiOI solution to adjust the pH to 10 to obtain a white solution, and 3 O 4 The nanoparticles, the sodium dodecylbenzene sulfonate and the BiOI solution are mixed, and then separated to obtain a yellow-brown precipitated powder, which is calcined to obtain Bi 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nanophotocatalyst.

[0008] The Fe 3 O 4 The magnetic nanoparticles are prepared by using ferric chloride hexahydrate, sodium acetate, ethylenediamine and ethylene glycol as raw materials.

[0009] The mass ratio of the ferric chloride hexahydrate, the sodium acetate, the ethylene glycol and the ethylenediamine is 1:4:30:2.

[0010] A kind of Bi 4 O 5 I 2 / Fe 3 O 4 The preparation method of the composite magnetic nano-photocatalyst comprises: S1, adding ferric chloride hexahydrate, sodium acetate and ethylenediamine into ethylene glycol, ultrasonically dispersing for 30 minutes, and then magnetically stirring for 1 hour until the solid reactants are completely dissolved;

[0011] The obtained mixed solution was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, and the reactor was sealed. After the reaction was completed, the solid was separated by centrifugation, washed, and dried to obtain a porous Fe 3 O 4 Nanoparticles;

[0012] S2, dissolving bismuth nitrate in an aqueous nitric acid solution to form solution A, and dissolving NaI in another aqueous nitric acid solution to form solution B;

[0013] S3, slowly adding solution B to solution A with continuous stirring to obtain a deep red BiOI solution;

[0014] S4, adding alkali solution to the BiOI solution to adjust the pH to 10 to obtain a white solution;

[0015] S5. Add Fe to the white solution. 3 O 4 The nanoparticles and sodium dodecylbenzene sulfonate are stirred until the sodium dodecylbenzene sulfonate is completely dissolved to obtain a mixed solution;

[0016] S6, transferring the mixed solution to a reactor for reaction to generate a yellow-brown precipitate, drying, and separating to obtain a yellow-brown precipitate powder;

[0017] S7. The yellow-brown precipitated powder was heated to 300-400°C and calcined for 2-4 hours under nitrogen atmosphere at a heating rate of 10°C / min to obtain Bi 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nanophotocatalyst.

[0018] In step S1, the reactor needs to be placed in an oven and heated to 180-220°C and reacted at a constant temperature for 5-7 hours, and then cooled to room temperature after the reaction is completed.

[0019] In step S2, the nitric acid aqueous solution is prepared by mixing concentrated nitric acid and water in a volume ratio of 1:1.

[0020] In step S5, the Fe 3 O 4 The amount of nanoparticles added is 10% of the mass percentage of the final composite magnetic nano-photocatalyst.

[0021] In step S6, the inner wall of the reactor is made of Teflon and needs to be heated to 120-180°C and then reacted at a constant temperature for 6-24 hours.

[0022] In step S6, a yellow-brown precipitate is separated by centrifugation, washed with distilled water and anhydrous ethanol, and then dried at 80°C for 6 hours to obtain a yellow-brown precipitate powder.

[0023] A kind of Bi 4 O 5 I 2 / Fe 3 O 4 The invention discloses a method for preparing a composite magnetic nanometer photocatalyst. The prepared composite magnetic nanometer photocatalyst is used for visible light catalytic degradation of antibiotic organic pollutants in water.

[0024] Technical effects and advantages of the present invention:

[0025] (1) Bi obtained by the present invention 4 O 5 I 2 / Fe 3 O 4 The composite magnetic nano-photocatalyst has a porous structure. On the one hand, the porous structure can improve the mobility of photogenerated carriers; on the other hand, it can adsorb more pollutants and provide more reactive sites for degradation reactions, thereby improving the catalytic degradation efficiency of antibiotics.

[0026] (2) Bi obtained by the present invention 4 O 5 I 2 / Fe 3 O 4 The composite magnetic nano-photocatalyst has superparamagnetic properties, and the use of an external magnetic field (such as a magnet) can quickly and effectively achieve material recycling, avoiding secondary pollution of the environment by powder materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Bi prepared in Example 1 of the present invention 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nanophotocatalyst, single Bi 4 O 5 I 2 Materials, Fe alone 3 O 4 XRD pattern of nanoparticles;

[0028] Figure 2 Bi prepared in Example 1 of the present invention 4 O 5 I 2 / Fe 3 O 4 SEM image of composite magnetic nano-photocatalyst;

[0029] Figure 3 For the present invention Bi 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nanophotocatalyst, commercial TiO 2 Comparison of the degradation effect of antibiotics (tetracycline hydrochloride) under visible light;

[0030] Figure 4 Bi prepared in Example 1 of the present invention 4 O 5 I 2 / Fe 3 O4 The effect diagram of the composite magnetic nano-photocatalyst being recycled and utilized five times to degrade antibiotics (tetracycline hydrochloride);

[0031] Figure 5 The Fe 3 O 4 Nanoparticle preparation flow chart;

[0032] Figure 6 Bi of the present invention 4 O 5 I 2 / Fe 3 O 4 Flow chart for the preparation of composite magnetic nanophotocatalysts. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] See also Figure 1-Figure 6 shown.

[0035] Embodiment 1

[0036] A kind of Bi 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nano photocatalyst, preparation method and application thereof are as follows:

[0037] (1) Adding ferric chloride hexahydrate, sodium acetate and ethylenediamine to ethylene glycol, wherein the mass ratio of ferric chloride hexahydrate, sodium acetate, ethylene glycol and ethylenediamine is 1:4:30:2, and ultrasonically dispersing for 30 minutes, and then magnetically stirring for 1 hour, until the solid reactant is completely dissolved; transferring the obtained mixed solution to a stainless steel reactor with a polytetrafluoroethylene liner, sealing the reactor, placing the reactor in an oven and heating it to 200° C. for constant temperature reaction for 6 hours, cooling it to room temperature after the reaction is completed, centrifuging and separating the solid, washing it, and drying it to obtain a porous structure of Fe 3 O 4 Nanoparticles;

[0038] (2) Concentrated nitric acid and water were mixed in a volume ratio of 1:1 to prepare a 50% nitric acid aqueous solution. 2 mmol Bi(NO 3 ) 3 ·5H 2O was dissolved in 30 ml of 50% nitric acid aqueous solution to form solution A, and 2 mmol of NaI was dissolved in another 30 ml of 50% nitric acid aqueous solution to form solution B;

[0039] (3) Slowly add solution B dropwise to solution A with continuous stirring to obtain a deep red BiOI solution;

[0040] (4) adding NaOH solution to the BiOI solution to adjust the pH to 10 to obtain a white solution;

[0041] (5) Add 10 mg Fe to the white solution 3 O 4 The nanoparticles and 1g of sodium dodecylbenzene sulfonate were stirred until the sodium dodecylbenzene sulfonate was completely dissolved to obtain a mixed solution;

[0042] (6) The mixed solution was transferred to a Teflon reactor, heated to 120° C., and reacted at this temperature for 12 h to generate a yellow-brown precipitate, which was dried and separated to obtain a yellow-brown precipitate powder;

[0043] (7) The yellow-brown precipitated powder was placed in a tube furnace and heated to 300 °C for calcination for 3 h under a nitrogen atmosphere at a heating rate of 10 °C / min to obtain Bi 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nanophotocatalyst.

[0044] The Bi prepared in Example 1 4 O 5 I 2 / Fe 3 O 4 The performance test characterization of the composite magnetic nano-photocatalytic material is as follows:

[0045] Figure 1 is Bi prepared in Example 1 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nanophotocatalyst, single Bi 4 O 5 I 2 Materials, Fe alone 3 O 4 XRD pattern of nanoparticles, * represents Bi 4 O 5 I 2 The peak of & represents Fe 3 O 4 The peak of Bi 4 O 5I 2 and Fe 3 O 4 Effective compounding, rather than simple physical mixing, is beneficial to improving the photocatalytic performance of the material.

[0046] Figure 2 is Bi prepared in Example 1 4 O 5 I 2 / Fe 3 O 4 The SEM image of the composite magnetic nano-photocatalytic material shows that Bi 4 O 5 I 2 / Fe 3 O 4 The composite magnetic nano-photocatalytic material is an ultra-thin nanosheet structure with a uniform and complete structure. The width of these nanosheets is about 150-300nm and the thickness is about 20nm.

[0047] Embodiment 2

[0048] (1) Adding ferric chloride hexahydrate, sodium acetate and ethylenediamine to ethylene glycol, wherein the mass ratio of ferric chloride hexahydrate, sodium acetate, ethylene glycol and ethylenediamine is 1:4:30:2, ultrasonically dispersing for 30 minutes, and then magnetically stirring for 1 hour until the solid reactant is completely dissolved; transferring the obtained mixed solution to a stainless steel reactor with a polytetrafluoroethylene liner, sealing the reactor, placing the reactor in an oven and heating it to 180° C. for constant temperature reaction for 7 hours, cooling to room temperature after the reaction is completed, centrifuging to separate the solid, washing, and drying to obtain a porous structure of Fe 3 O 4 Nanoparticles;

[0049] (2) Concentrated nitric acid and water were mixed in a volume ratio of 1:1 to prepare a 50% nitric acid aqueous solution. 2 mmol Bi(NO 3 ) 3 ·5H 2 O was dissolved in 30 ml of 50% nitric acid aqueous solution to form solution A, and 2 mmol of NaI was dissolved in another 30 ml of 50% nitric acid aqueous solution to form solution B;

[0050] (3) Slowly add solution B dropwise to solution A with continuous stirring to obtain a deep red BiOI solution;

[0051] (4) adding NaOH solution to the BiOI solution to adjust the pH to 10 to obtain a white solution;

[0052] (5) Add 10 mg Fe to the white solution 3 O 4The nanoparticles and 1g of sodium dodecylbenzene sulfonate were stirred until the sodium dodecylbenzene sulfonate was completely dissolved to obtain a mixed solution;

[0053] (6) The mixed solution was transferred to a Teflon reactor, heated to 120° C., and reacted at this temperature for 12 h to generate a yellow-brown precipitate, which was dried and separated to obtain a yellow-brown precipitate powder;

[0054] (7) The yellow-brown precipitated powder was placed in a tube furnace and heated to 300 °C for calcination for 3 h under a nitrogen atmosphere at a heating rate of 10 °C / min to obtain Bi 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nanophotocatalyst.

[0055] Embodiment 3

[0056] (1) Adding ferric chloride hexahydrate, sodium acetate and ethylenediamine to ethylene glycol, wherein the mass ratio of ferric chloride hexahydrate, sodium acetate, ethylene glycol and ethylenediamine is 1:4:30:2, and ultrasonically dispersing for 30 minutes, and then magnetically stirring for 1 hour, until the solid reactant is completely dissolved; transferring the obtained mixed solution to a stainless steel reactor with a polytetrafluoroethylene liner, sealing the reactor, placing the reactor in an oven and heating it to 200° C. for constant temperature reaction for 6 hours, cooling it to room temperature after the reaction is completed, centrifuging and separating the solid, washing it, and drying it to obtain a porous structure of Fe 3 O 4 Nanoparticles;

[0057] (2) Concentrated nitric acid and water were mixed in a volume ratio of 1:1 to prepare a 50% nitric acid aqueous solution. 2 mmol Bi(NO 3 ) 3 ·5H 2 O was dissolved in 30 ml of 50% nitric acid aqueous solution to form solution A, and 2 mmol of NaI was dissolved in another 30 ml of 50% nitric acid aqueous solution to form solution B;

[0058] (3) Slowly add solution B dropwise to solution A with continuous stirring to obtain a deep red BiOI solution;

[0059] (4) adding NaOH solution to the BiOI solution to adjust the pH to 10 to obtain a white solution;

[0060] (5) Add 50 mg Fe to the white solution 3 O 4 The nanoparticles and 1g of sodium dodecylbenzene sulfonate were stirred until the sodium dodecylbenzene sulfonate was completely dissolved to obtain a mixed solution;

[0061] (6) The mixed solution was transferred to a Teflon reactor, heated to 120° C., and reacted at this temperature for 12 h to generate a yellow-brown precipitate, which was dried and separated to obtain a yellow-brown precipitate powder;

[0062] (7) The yellow-brown precipitated powder was placed in a tube furnace and heated to 300 °C for calcination for 3 h under a nitrogen atmosphere at a heating rate of 10 °C / min to obtain Bi 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nanophotocatalyst.

[0063] Embodiment 4

[0064] (1) Adding ferric chloride hexahydrate, sodium acetate and ethylenediamine to ethylene glycol, wherein the mass ratio of ferric chloride hexahydrate, sodium acetate, ethylene glycol and ethylenediamine is 1:4:30:2, and ultrasonically dispersing for 30 minutes, and then magnetically stirring for 1 hour, until the solid reactant is completely dissolved; transferring the obtained mixed solution to a stainless steel reactor with a polytetrafluoroethylene liner, sealing the reactor, placing the reactor in an oven and heating it to 200° C. for constant temperature reaction for 6 hours, cooling it to room temperature after the reaction is completed, centrifuging and separating the solid, washing it, and drying it to obtain a porous structure of Fe 3 O 4 Nanoparticles;

[0065] (2) Concentrated nitric acid and water were mixed in a volume ratio of 1:1 to prepare a 50% nitric acid aqueous solution. 2 mmol Bi(NO 3 ) 3 ·5H 2 O was dissolved in 30 ml of 50% nitric acid aqueous solution to form solution A, and 2 mmol of NaI was dissolved in another 30 ml of 50% nitric acid aqueous solution to form solution B;

[0066] (3) Slowly add solution B dropwise to solution A with continuous stirring to obtain a deep red BiOI solution;

[0067] (4) adding NaOH solution to the BiOI solution to adjust the pH to 10 to obtain a white solution;

[0068] (5) Add 10 mg Fe to the white solution 3 O 4 The nanoparticles and 1g of sodium dodecylbenzene sulfonate were stirred until the sodium dodecylbenzene sulfonate was completely dissolved to obtain a mixed solution;

[0069] (6) The mixed solution was transferred to a Teflon reactor, heated to 150° C., and reacted at a constant temperature for 24 h to generate a yellow-brown precipitate, which was dried and separated to obtain a yellow-brown precipitate powder;

[0070] (7) The yellow-brown precipitated powder was placed in a tube furnace and heated to 300 °C for calcination for 3 h under a nitrogen atmosphere at a heating rate of 10 °C / min to obtain Bi 4 O 5 I 2 / Fe 3 O 4 Composite magnetic nanophotocatalyst.

[0071] Embodiment 5

[0072] Bi prepared in Example 1 4 O 5 I 2 / Fe 3 O 4 The composite magnetic nano-photocatalytic material was used as a photocatalyst to catalyze the degradation of tetracycline hydrochloride aqueous solution (TCH) under visible light conditions, where the concentration of TCH was 40 mg / L. The specific operation is as follows:

[0073] Add photocatalyst (0.02 g) to 100 ml of TCH aqueous solution and stir for 30 min in a dark environment to reach adsorption equilibrium; sample 3 ml after standing, and then place the beaker under a 150 W xenon lamp with a 420 nm cutoff filter, sampling 3 ml every 20 min until 140 min.

[0074] The sample was centrifuged and the supernatant was used to measure the content of tetracycline hydrochloride in high performance liquid chromatography.

[0075] The photocatalysts were replaced with commercial titanium dioxide, Bi prepared in Example 1, 4 O 5 I 2 / Fe 3 O 4 The composite magnetic nano-photocatalytic material and the blank sample without catalyst were subjected to the photocatalytic degradation test using the same operation method as above, with other conditions unchanged. The catalytic degradation effects of various catalysts on TCH are shown in Figure 3 .

[0076] Depend on Figure 3 It can be seen that Bi 4 O 5 I 2 / Fe 3 O 4 When the composite magnetic nano-photocatalyst was irradiated with visible light for 100 min, the composite photocatalyst completely degraded 100 mL of 40 mg / L TC solution; while the commercial TiO 2 There is basically no degradation effect on TC at this concentration under visible light. In comparison, the Bi prepared in the present invention 4 O 5 I2 / Fe 3 O 4 Composite magnetic nanophotocatalytic materials exhibit the best catalytic performance.

[0077] Therefore, the Bi 4 O 5 I 2 / Fe 3 O 4 The composite magnetic nano-photocatalytic material has significant visible light photocatalytic activity and can completely catalyze the degradation of antibiotic organic pollutants under the condition of extremely small catalyst dosage.

[0078] Embodiment 6

[0079] Recover the photocatalyst in the solution after the photocatalytic degradation experiment in Example 5: Use the external magnetic field-magnet adsorption effect to remove Bi in the water 4 O 5 I 2 / Fe 3 O 4 After the composite magnetic nano-photocatalytic material was adsorbed, recovered, washed and dried, it was reused to degrade TCH solution. After the degradation experiment, the catalyst was recovered by magnets and reused for the third time. It was recycled five times in total. The catalytic degradation effect of these five recyclings was shown in Figure 2. Figure 4 .

[0080] It can be seen that after five cycles, the degradation rate of the photocatalyst remains unchanged, indicating that the Bi 4 O 5 I 2 / Fe 3 O 4 The composite magnetic nano-photocatalytic material has good stability in water and can be reused many times.

[0081] In summary, the present invention provides a Bi 4 O 5 I 2 / Fe 3 O 4 Compared with existing commercial photocatalysts, composite magnetic nanophotocatalysts have better visible light degradation effects, and can use external magnetic fields (such as magnets) to quickly and effectively recycle materials, avoiding secondary environmental pollution and greatly reducing the cost of using photocatalysts.

[0082] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0083] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst, characterized in that: The invention comprises Fe3O4 nanoparticles with a porous structure, sodium dodecylbenzene sulfonate and BiOI solution. Alkali solution is added to the BiOI solution to adjust the pH value to 10 to obtain a white solution. The Fe3O4 nanoparticles, sodium dodecylbenzene sulfonate and BiOI solution are mixed and then separated to obtain a yellow-brown precipitated powder. After calcination, a Bi4O5I2 / Fe3O4 composite magnetic nano photocatalyst is obtained.

2. The Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst according to claim 1, characterized in that: The Fe3O4 magnetic nanoparticles are prepared by using ferric chloride hexahydrate, sodium acetate, ethylenediamine and ethylene glycol as raw materials.

3. The Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst according to claim 2, characterized in that: The mass ratio of the ferric chloride hexahydrate, the sodium acetate, the ethylene glycol and the ethylenediamine is 1:4:30:

2.

4. A method for preparing a Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst, based on the method for preparing a Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst according to any one of claims 1 to 3, characterized in that: S1. Add ferric chloride hexahydrate, sodium acetate and ethylenediamine to ethylene glycol, disperse by ultrasonic for 30 minutes, and then stir by magnetic stirring for 1 hour until the solid reactants are completely dissolved; The obtained mixed solution is transferred to a stainless steel reactor with a polytetrafluoroethylene liner, and the reactor is sealed. After the reaction is completed, the solid matter is separated by centrifugation, washed, and dried to obtain Fe3O4 nanoparticles with a porous structure; S2, dissolving bismuth nitrate in an aqueous nitric acid solution to form solution A, and dissolving NaI in another aqueous nitric acid solution to form solution B; S3, slowly adding solution B to solution A with continuous stirring to obtain a deep red BiOI solution; S4, adding alkali solution to the BiOI solution to adjust the pH to 10 to obtain a white solution; S5, adding Fe3O4 nanoparticles and sodium dodecylbenzene sulfonate to the white solution, stirring until the sodium dodecylbenzene sulfonate is completely dissolved to obtain a mixed solution; S6, transferring the mixed solution to a reactor for reaction to generate a yellow-brown precipitate, drying, and separating to obtain a yellow-brown precipitate powder; S7. The yellow-brown precipitated powder was heated to 300-400°C and calcined for 2-4 hours under a nitrogen atmosphere at a heating rate of 10°C / min to obtain a Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst.

5. The method for preparing the Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst according to claim 4, characterized in that: In step S1, the reactor needs to be placed in an oven and heated to 180-220°C and reacted at a constant temperature for 5-7 hours, and then cooled to room temperature after the reaction is completed.

6. The method for preparing the Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst according to claim 4, characterized in that: In step S2, the nitric acid aqueous solution is prepared by mixing concentrated nitric acid and water in a volume ratio of 1:

1.

7. The method for preparing the Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst according to claim 4, characterized in that: In step S5, the amount of Fe3O4 nanoparticles added is 10% by weight of the final composite magnetic nano-photocatalyst.

8. The method for preparing the Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst according to claim 4, characterized in that: In step S6, the temperature needs to be raised to 120-180° C., and then the reaction is carried out at a constant temperature for 6-24 hours.

9. The method for preparing the Bi4O5I2 / Fe3O4 composite magnetic nano-photocatalyst according to claim 4, characterized in that: In step S6, a yellow-brown precipitate is separated by centrifugation, washed with distilled water and anhydrous ethanol, and then dried at 80°C for 6 hours to obtain a yellow-brown precipitate powder.

Citation Information

Patent Citations

  • Preparation and application of magnetic visible light catalyst Fe3O4@Bi2O3-BiOBr-BiOI

    CN106140207A

  • Preparation method of composite photocatalytic material of Fe3O4-N doped with Ni / Zn-MOFs / g-C3N4

    CN108579819A

  • Eu-doped Bi4O5I2 composite nanometer photocatalyst and preparation method thereof

    CN108927182A

  • Bi4O5I2 / Bi5O7I composite photocatalyst as well as preparation method and application thereof

    CN113101952A